2018
DOI: 10.1108/cg-09-2017-0213
|View full text |Cite
|
Sign up to set email alerts
|

Women directors’ propensity towards risk in technology firms

Abstract: Purpose This study aims to investigate the impact of the presence of women directors on firm’s risk-taking behavior in industries where innovation is pivotal and how this impact varies across ownership structure. Design/methodology/approach A sample of 71 listed technology firms on the National Stock Exchange of India for the period of 2008 to 2013 was used. Generalized method of moment estimation technique was used for data analysis. Findings Results reveal a positive impact of the presence of women direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…Family firms are commercial organisations in which various generations of the same family influence the decision-making processes as well as the capacity to shape the visions and behaviours of companies and the will of the company in achieving its distinctive objectives (Lee et al , 2017; Mukarram et al , 2018; Panicker, 2017; Ye et al , 2019) and generally identified in the short term by means of the family leadership or ownership. For a company to classify as a family firm, there has to be a multi-generational and preponderant family dimension that ensures the unique dynamics and relationships ongoing in family firms (Chaudhary and Batra, 2018; Hussain and Ismail, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Family firms are commercial organisations in which various generations of the same family influence the decision-making processes as well as the capacity to shape the visions and behaviours of companies and the will of the company in achieving its distinctive objectives (Lee et al , 2017; Mukarram et al , 2018; Panicker, 2017; Ye et al , 2019) and generally identified in the short term by means of the family leadership or ownership. For a company to classify as a family firm, there has to be a multi-generational and preponderant family dimension that ensures the unique dynamics and relationships ongoing in family firms (Chaudhary and Batra, 2018; Hussain and Ismail, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This study would contribute to the literature as it focuses on the impact of board gender diversity on firm performance in the information technology (IT) sector of the United States (US). Prior literature that investigated high-technology companies was focused on female directors and earnings management (Gavious et al 2012) or risk (Mukarram et al 2018). Carmen, (2019) merely explored gender diversity in US computer industries but only at the senior management level.…”
mentioning
confidence: 99%
“…Ten empirical quantitative articles reviewed consider the direct influence of gender-related variable on innovation in terms of TMT gender diversity. These studies primarily adopt the upper echelons theory in conjunction with agency theory (Midavaine et al , 2016; Mukarram et al , 2018), behavioural theory (Iren and Tee, 2018) or relational demography (Heyden et al , 2018; Lyngsie and Foss, 2017) to explain why gender diversity influences innovation.…”
Section: Group C - Quantitative Empirical Studiesmentioning
confidence: 99%
“…Several innovation variables have been studied in our sample of studies in typology 1. On the input side, the influence of TMT diversity on R&D spending (Midavaine et al , 2016; Mukarram et al , 2018) has been studied. On the output side, product innovation (Galia and Zenou, 2012; Talke et al , 2011), marketing innovation (Heyden et al , 2018) and intellectual capital efficiency (Nadeem et al , 2019) have been studied, leaving much to be desired about other types of innovation such as organizational innovation.…”
Section: Group C - Quantitative Empirical Studiesmentioning
confidence: 99%